Using Peptidomimetics and Constrained Peptides as Valuable Tools for Inhibiting Protein⁻Protein Interactions. - Robertson, Naomi S; Spring, David R (MDPI, 2018)
Protein⁻protein interactions (PPIs) are tremendously important for the function of many biological processes. However, because of the structure of many protein⁻protein interfaces (flat, featureless and relatively large), they have largely been overlooked as potential drug targets. In this review, we highlight the current tools used to study the molecular recognition of PPIs through the use of different peptidomimetics, from small molecules and scaffolds to peptides. Then, we focus on constrained peptides, and in particular, ways to constrain α-helices through stapling using both one- and two-component techniques.
Keywords: macrocycles; peptidomimetics; protein–protein interactions; proteomimetics; stapled peptides; Peptides; Peptidomimetics; Protein Binding